Optimization of Heating Time for Natural Rubber Motorcycle Inner Tire Patches - Sulaiman, Zaid; Bagas Akbar Gumelar; Lazuardi Akmal Islami; Muhammad Bagas Ananda (Universitas Medan Area, 2024)
Tires have the main function of the vehicle to sustain the strength of the vehicle. Damage to tires that often occurs is punctured and broken. One way to repair it is by patching the inner tube. The purpose of this study was to find out the optimal heating time when patching tires. Tires are said to have optimal strength when they have strong adhesion and have no defects when given air pressure. The sample preparation method used is conventional tire patching. The tests carried out were adhesive testing, macro testing, FTIR testing, and thickness testing. The inner tube used is natural rubber. The test results show that the heating time of 15 minutes has the highest adhesive strength and the bond between the tire patch and the patch glue is well connected. However, the longer the heating time, the thinner the inner tube becomes. The thinner the inner tube causes the